2020
DOI: 10.1177/0363546520929353
|View full text |Cite
|
Sign up to set email alerts
|

Scapular Morphologic Characteristics and Rotator Cuff Tear Pattern Are Independently Associated With Chronic Pseudoparalyis: A Matched-Pair Analysis of Patients With Massive Rotator Cuff Tears

Abstract: Background: It is unclear which structural parameters determine the development or the absence of chronic pseudoparalysis (PP) in patients with massive rotator cuff tears (mRCTs). Purpose: To determine whether scapular morphologic characteristics and extent of rotator cuff tearing are independent factors associated with chronic PP. Study Design: Case-control study; Level of evidence, 3. Methods: In this retrospective case-control study, 50 patients with chronic mRCT (≥2 fully detached tendons) and active scapu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…The concept of a direct relationship of chronic pseudoparalysis with RCT size and anterior tear involvement was reported previously. 2,12,43 However, the definition of pseudoparalysis has raised controversial discussions. Critics have noted that 90° of painless and neurologically unimpaired active scapular plane abduction is an incorrect cutoff value for pseudoparalysis, as maintaining 90° equals 55% of full active elevation, 1 which appears to be weak (paretic) rather than paralytic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of a direct relationship of chronic pseudoparalysis with RCT size and anterior tear involvement was reported previously. 2,12,43 However, the definition of pseudoparalysis has raised controversial discussions. Critics have noted that 90° of painless and neurologically unimpaired active scapular plane abduction is an incorrect cutoff value for pseudoparalysis, as maintaining 90° equals 55% of full active elevation, 1 which appears to be weak (paretic) rather than paralytic.…”
Section: Discussionmentioning
confidence: 99%
“…11,13,21 In patients with chronic pseudoparalysis, a clear association between the size and location of the RCT has been described. Of underlying importance is the integrity of the inferior half of the subscapularis tendon 2,5,12,43 ; however, a biomechanical explanation for this phenomenon is still missing.…”
mentioning
confidence: 99%
“…Obvious dynamic anterosuperior subluxation of the humerus upon resisted abduction is suggestive of an irreparable posterosuperior with additional subscapularis tear. In case of complete pseudoparalysis and/or a dynamic anterosuperior escape of the humeral head, which is most likely associated with an irreparable subscapularis tear [27][28][29], a LDT will not be able to substantially improve shoulder function and is therefore not indicated in such severely functionally impaired shoulders.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Definitions of this condition vary, but loss of active shoulder elevation or abduction in the scapular plane beyond 90° are commonly cited. 10,33 A 2017 systematic review of pseudoparalysis mentioned SCR among the possible treatments 33 but observed that, to date, the SCR literature had not specifically addressed this topic. The following year, however, Mihata et al 20 published a study that tackled this issue, “Arthroscopic Superior Capsule Reconstruction Can Eliminate Pseudoparalysis in Patients With Irreparable Rotator Cuff Tears.” Among 88 patients with irreparable cuff tears, they identified 28 with moderate and 15 with severe pseudoparalysis, distinguished by the absence or presence of a drop-arm sign.…”
mentioning
confidence: 99%
“…In the setting of large to massive rotator cuff tears, pseudoparalysis has been linked to the extent of the tear and specifically to the involvement of the subscapularis. 4,7,10,32 In the July 2020 AJSM , Takayama et al 32 reported success using SCR to reverse pseudoparalysis, except in patients with irreparable subscapularis tears. In the December 2020 AJSM , Mihata et al 21 compared outcomes after SCR in patients with and without subscapularis tears.…”
mentioning
confidence: 99%